The two C. elegans class VI myosins, SPE-15/HUM-3 and HUM-8, share similar motor properties, but have distinct developmental and tissue expression patterns - Behbehani, Ranya; Johnson, Chloe; Holmes, Alexander J.; Gratian, Matthew J.; Mulvihill, Daniel P.; Buss, Folma (Frontiers in Physiology, 2024)
Myosins of class VI move toward the minus-end of actin filaments and play vital roles in cellular processes such as endocytosis, autophagy, protein secretion, and the regulation of actin filament dynamics. In contrast to the majority of metazoan organisms examined to date which contain a single MYO6 gene, C. elegans, possesses two MYO6 homologues, SPE-15/HUM-3 and HUM-8. Through a combination of in vitro biochemical/biophysical analysis and cellular assays, we confirmed that both SPE-15/HUM-3 and HUM-8 exhibit reverse directionality, velocities, and ATPase activity similar to human MYO6. Our characterization also revealed that unlike SPE-15/HUM-3, HUM-8 is expressed as two distinct splice isoforms, one with an additional unique 14 amino acid insert in the cargo-binding domain. While lipid and adaptor binding sites are conserved in SPE-15/HUM-3 and HUM-8, this conservation does not enable recruitment to endosomes in mammalian cells. Finally, we performed super-resolution confocal imaging on transgenic worms expressing either mNeonGreen SPE-15/HUM-3 or wrmScarlet HUM-8. Our results show a clear distinction in tissue distribution between SPE-15/HUM-3 and HUM-8. While SPE-15/HUM-3 exhibited specific expression in the gonads and neuronal tissue in the head, HUM-8 was exclusively localized in the intestinal epithelium.Overall, these findings align with the established tissue distributions and localizations of human MYO6. 2004;Arden et al, 2016). Interestingly, MYO6 overexpression is commonly observed in diverse cancers, including prostate and ovarian cancer (Yoshida et al, 2004;Dunn et al, 2006).